2001
DOI: 10.1097/00002371-200103000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Sequential 5-Aza-2’-deoxycytidine-Depsipeptide FR901228 Treatment Induces Apoptosis Preferentially in Cancer Cells and Facilitates Their Recognition by Cytolytic T Lymphocytes Specific for NY-ESO-1

Abstract: Global alterations in chromatin structure profoundly influence gene expression in thoracic neoplasms, silencing tumor suppressors while facilitating the expression of various cancer testis antigens such as NY-ESO-1. Although recent studies have shown that histone deacetylase inhibitors can potentiate tumor suppressor gene induction mediated by demethylating agents in cancer cells, the ability of these agents to augment cancer testis antigen expression have not been fully defined. The authors designed the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 43 publications
9
123
0
1
Order By: Relevance
“…Additionally, it may be possible to up-regulate NY-ESO-1 expression in cancer patients by treatment with drugs that induce DNA demethylation (38,39). Finally, we have identified MHC class II-restricted NY-ESO-1 TCR epitopes (22,40,41), and we are currently attempting to simultaneously engineer a population of T cells with both class Iand class II-restricted TCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it may be possible to up-regulate NY-ESO-1 expression in cancer patients by treatment with drugs that induce DNA demethylation (38,39). Finally, we have identified MHC class II-restricted NY-ESO-1 TCR epitopes (22,40,41), and we are currently attempting to simultaneously engineer a population of T cells with both class Iand class II-restricted TCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous microarray study (Karpf et al, 2004), we observed that treatment with DAC, a classical DNMT inhibitor (Christman, 2002), elicited robust dose-dependent induction of CG-X antigen genes in the colorectal cancer cell lines HCT116 and RKO (Supplemental Figure 1a-c). Based on previous reports (Cameron et al, 1999;Weiser et al, 2001), we investigated whether treatment with the histone deacetylase (HDAC) inhibitor Trichostatin A (TSA) enhances the ability of DAC to activate CG-X antigen gene expression. TSA treatment slightly augmented DAC-mediated induction of CG-X antigen expression (Supplemental Figure 1a-c), as did TSA treatment alone, in both cell types (Supplemental Figure 1b and activation of CG-X antigen gene expression is associated with promoter methylation changes, we examined CG-X antigen gene promoter methylation before and after DAC treatment using methylation-specific PCR (MSP) (Herman et al, 1996).…”
Section: Activation Of Cg-x Antigen Gene Expression By Dac Treatmentmentioning
confidence: 99%
“…The first evidence of a role for DNA methylation in the regulation of CG-X antigen expression was provided by experiments using the DNA methyltransferase inhibitor 5-aza-2 0 -deoxycytidine (DAC) (Weber et al, 1994). Subsequently, the expression of several CG-X antigen genes was shown to inversely correlate with promoter methylation, and to be responsive to activation by DNA methyltransferase inhibitors (De Smet et al, 1996Weiser et al, 2001;Sigalotti et al, 2002;Karpf et al, 2004). CG-X gene expression has also been postulated, based on data in human melanoma cell lines, to be associated with global genomic DNA hypomethylation (De Smet et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Based on duplicates of each condition (pre and post treatment), a threshold of 2-fold change in expression relative to control expression of each gene was reported as the ratio of the value obtained for each condition relative to control conditions after data normalization. 7 Statistical methods. Mean changes across time on DNA methylation and HbF from baseline to each follow-up time point were tested with the one-sample (dependent) t test and the one-sample nonparametric test.…”
Section: Gene Expression Analysismentioning
confidence: 99%